Implementasi Program Adiwiyata Dalam Mewujudkan Karakter Peduli Lingkungan Peserta Didik - Parasih; Siska Septia Ulfa; Leny Marlina; Asri Karolina (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The Adiwiyata program, launched by the Ministry of Environment and Forestry, aims to create schools that care and cultivate the environment. The program not only focuses on implementing a green environment in schools, but also integrating environmental values into the learning process. This study aims to determine the implementation of the Adiwiyata program in realizing the character of environmental care in students at SD Negeri 15 Talang Ubi. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation. In analyzing the data, researchers used Miles and Huberman data analysis, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that the implementation of the Adiwiyata program at SD Negeri 15 Talang Ubi in realizing the environmental care character of students was carried out systematically by involving various school elements, such as teachers, students, and the surrounding community. The program includes waste management activities, reforestation, and integration of environmental materials in the curriculum. Students' active participation in various environmental activities also plays an important role in realizing the character of environmental care. In conclusion, the Adiwiyata program has successfully fostered the character of environmental care in students through a holistic and collaborative approach.